An exploration of adult nurses' attitudes towards patients with AN: a student's experience of research - Emily, Rushworth (2014)
Abstract This paper explores the experience of conducting clinical research on adult nurses' attitudes towards individuals with a diagnosis of Anorexia Nervosa (AN) from the perspective of an undergraduate mental health nursing student. The original intention of this paper was to use a grounded theory research approach to explore the attitudes that currently exist amongst adult nurses towards those with AN. A qualitative questionnaire was developed for use as the research instrument for this research project, and four adult ward settings chosen for study, based upon their relevance to the physical symptoms of AN and consequent likelihood to provide care for those with a diagnosis of AN. However, as the research journey progressed, a number of difficulties were encountered and negotiation of access to adult settings and the recruitment of participants proved to be major hindrances in the data collection process. This necessitated a shift in the focus of the paper towards an exploration of the researcher's experience in attempting to conduct the study. This paper provides a discussion of these challenges in the context of the current nursing environment, using relevant literature to provide an informed critique of the issues. It concludes by drawing key implications from this discussion. The first implication is that of the personal development that this project has facilitated, and the second is that of recommendations that have been indicated for individuals intending to conduct mental health research in non-mental health settings.